The rise of Christianity through the eyes of Gibbon, Harnack and Rodney Stark: a valedictory lecture on the occasion of his retirement from the chair of Religious Studies, in the Faculty of Theology and Religious Studies, delivered in abbreviated form before the University of Groningen on 29 January 2010 - Bremmer, Jan N. (Barkhuis, 2010)
"The rise of Christianity up to the victory of Constantine has often been studied and remains a puzzling phenomenon. In this valedictory lecture Jan N. Bremmer concentrates on the explanations adduced, focusing in particular on the works of three iconic figures from the last two hundred and fifty years: "The History of the Decline and Fall of the Roman Empire" of Edward Gibbon, the most famous ancient historian of all time, at the end of the eighteenth century; "Die Mission und Ausbreitung des Christentums" of Adolf von Harnack, the greatest historian of early Christianity of all time, around 1900, and "The Rise of Christianity" of Rodney Stark, the most adventurous sociologist of religion of our times, at the end of the twentieth century. Bremmer locates their concerns and explanations within their own times, but also takes them seriously as scholars, discussing their analyses and approaches. In this way he shows both the continuities and the innovations in the evolving view which scholarship presents of early Christianity"--P. 4 of cover